Male or Female, who is better? Students' Perceptions of Mathematics Physics E-Module Based on Gender - Astalin Astalin; Darmaji Darmaji; Dwi Agus Kurniawan; Mashelin Wulandari (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2021)
This study aims to determine student perceptions of the physics-mathematical e-module based on gender differences. This type of research is quantitative research. This research targets the students of the physics education study program at the Jambi University class of 2019, consisting of classes A, B, and C with a research sample of 120 people using simple random sampling. Data analysis was carried out descriptively and used normality, homogeneity, and ANOVA tests. The results of the Anova test showed that there were differences in perceptions based on gender, with a significance of 0.018 for females and 0.025 for males, which means that there are differences in student perceptions. Furthermore, this difference can be seen in the LSD follow up test where there are two classes for the female gender, which have significant differences in perception in class A and class C with a significance of 0.044 and classes B and C with a significance 0.011 for the female gender. Meanwhile, in the male gender, only classes B and C have a significant difference with a significance value of 0.07. However, overall, students gave a good perception of this e-module so that this e-module can be used in learning mathematics and physics on partial differential material.